Meningitis associated with sulphasalazine in a patient with Sjögren's syndrome and polyarthritis. Issue 9 (September 1991) - Merrin, P; Williams, I A
Abstract : A case of meningitis occurring in a 37 year old woman with Sjögren's syndrome, seropositive arthritis, and a possible overlap syndrome soon after starting sulphasalazine and after subsequent rechallenge is reported.